2020
DOI: 10.5194/tc-2020-31
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Present-day and future Greenland Ice Sheet precipitation frequency from satellite observations and an Earth System Model

Abstract: Abstract. The dominant mass input component of the Greenland Ice Sheet (GrIS) is precipitation, whose amounts and phase are poorly constrained by observations. Here we use spaceborne radar observations from CloudSat to map the precipitation frequency and phase on the GrIS, and use those observations, in combination with a satellite simulator to enable direct comparison between observations and model, to evaluate present-day precipitation frequency in the Community Earth System Model (CESM). The observations sh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…. Two recent studies have used CloudSat's CPR to look at snowfall over the GIS in particular: Lenaerts et al (2019) focused on GIS snowfall frequency and leveraged the satellite observations to evaluate climate model output; and Bennartz et al (2019) used the radar measurements to provide the first in-depth, observationally based snowfall rate estimates of the GIS.…”
mentioning
confidence: 99%
“…. Two recent studies have used CloudSat's CPR to look at snowfall over the GIS in particular: Lenaerts et al (2019) focused on GIS snowfall frequency and leveraged the satellite observations to evaluate climate model output; and Bennartz et al (2019) used the radar measurements to provide the first in-depth, observationally based snowfall rate estimates of the GIS.…”
mentioning
confidence: 99%
“…In Chapter 4, we described model progress towards CESM2, and presented a detailed assessment of GrIS surface energy and mass balance (SEB and SMB) using six historical ensemble members. A complementary study by Lenaerts et al [2020a] demonstrated that the Community Atmosphere Model version 6 (CAM6, the atmosphere component in CESM2) is so far the best CAM version for modelling clouds over Greenland, which further adds confidence to our results. On balance, we conclude that CESM2 is a capable tool in modelling GrIS SMB in a physically-based way, and is likely one of the few ESMs that can currently do this.…”
Section: General Conclusion From This Thesissupporting
confidence: 76%
“…This aligns with our results in Chapter 5, where we favorably compare cloud output from coupled CESM2 simulations to Cloudsat-CALIPSO. However, both our study and [Lenaerts et al, 2020a] indicate that the representation of clouds in CAM6 is not perfect, as for instance illustrated by biases in ice water path and longwave cloud forcing.…”
Section: Challenge 2: Atmospheric Forcingmentioning
confidence: 68%
See 1 more Smart Citation
“…Since the beginning of DO-Op, the CPR has collected data primarily during only the sunlit portion of the orbit. While many studies have so far used data from the Full Operations (Full-Op) period prior to the battery anomaly [4,7,14,15], the need for more recent CloudSat observations for comparison against new sensors such as the Global Precipitation Measurement (GPM) Core Observatory [16,17] or for the recent validation and optimization of models in a changing climate have increasingly required the use of the DO-Op observations as well [5,9,18,19]. This study compares CloudSat snowfall measurements taken during the Full-Op period against those taken during the DO-Op period to assess the impact of this change in sampling on snowfall properties estimated from the CloudSat snowfall product.…”
Section: Introductionmentioning
confidence: 99%